2015
DOI: 10.1007/s00705-014-2315-9
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Nef and INI1/SMARCB1 augments replicability of HIV-1 in resting human peripheral blood mononuclear cells

Abstract: A central feature of HIV-1 infection is the inability of entering virus to integrate into chromosomes of resting T lymphocytes unless they are mitogenically activated. In contrast, SIVpbj1.9 replicates in initially resting T lymphocytes by activating infected cells. Previous reports have shown that a difference in Nef-mediated T cell activation between HIV-1 and SIVpbj1.9 plays a critical role in the differing abilities of these viruses to replicate in resting lymphocytes. However, the molecular details of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Alternatively, USP15 could activate other cellular protein(s) in the USP15/Nef complex, and the activated protein(s) in turn degrades Nef protein. We accordingly screened for a potential cellular component involved in the UPS-mediated protein degradation by interacting with Nef, using the yeast- followed by the mammalian-two-hybrid assays (Kalpana et al, 1994; Pyeon and Park, 2015). We found that Nef binds to ubiquitin-protein ligase E3A (UBE3A/E6AP) which induces protein degradation by attaching Ub to substrates (Bernassola et al, 2008; Vande Pol and Klingelhutz, 2013), i.e.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alternatively, USP15 could activate other cellular protein(s) in the USP15/Nef complex, and the activated protein(s) in turn degrades Nef protein. We accordingly screened for a potential cellular component involved in the UPS-mediated protein degradation by interacting with Nef, using the yeast- followed by the mammalian-two-hybrid assays (Kalpana et al, 1994; Pyeon and Park, 2015). We found that Nef binds to ubiquitin-protein ligase E3A (UBE3A/E6AP) which induces protein degradation by attaching Ub to substrates (Bernassola et al, 2008; Vande Pol and Klingelhutz, 2013), i.e.…”
Section: Discussionmentioning
confidence: 99%
“…For RT assay, virions in the supernatant were pelleted by centrifugation at 12,000 g for 1 h, and the RT activity was determined, as described (Pyeon and Park, 2015). For virion preparation for WB, cells and cell debris in the culture supernatant were removed by centrifugation at 800 g for 100 min, and the cleared supernatant was passed through a 0.22 μm filter (Corning, NY) to ensure complete removal of smaller cell debris.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…His-tagged HIV-1 INT was purified using Ni-NTA agarose beads (QIAGEN, Valencia, CA) from overnight culture of BL21 cells transformed with pINSD.His.Sol, obtained from Dr. Robert Craigie through the AIDS Research and Reference Reagent Program, Division of AIDS, NIAID, NIH. The in vitro DNA strand transfer assay was then performed, using purified INT and INI1 as described previously [4, 8]. Briefly, the HIV-1 INT substrate U5.5 (5′-GGATCCGGAAAA TCTCTAGCA) was labeled with 50 μCi of [γ- 32 P]ATP (NEN) by incubating with 10 U of T4 polynucleotide kinase (New England Biolabs, Beverly, MA).…”
Section: Methodsmentioning
confidence: 99%
“…Our recent studies have revealed that the Nef protein of simian immunodeficiency virus PBj1.9 enhanced proviral DNA integration into the host chromosome in association with INT and human INI1 [8]. To verify that simian INI1 also has the same function in proviral DNA integration, we sequenced simian INI1 cDNA and compared its function with that of its human counterpart.…”
Section: Introductionmentioning
confidence: 99%